Ordered mesoporous metal oxides for electrochemical applications: correlation between structure, electrical properties and device performance. Issue 18 (12th April 2021) - Celik, Erdogan; Ma, Yanjiao; Brezesinski, Torsten; Elm, Matthias T.
Abstract : In this Perspective, the authors review the interplay between structure and charge-transport properties of mesoporous metal oxides, with an emphasis on applications in electrochemical energy storage, catalysis and gas sensing. Abstract : Ordered mesoporous metal oxides with a high specific surface area, tailored porosity and engineered interfaces are promising materials for electrochemical applications. In particular, the method of evaporation-induced self-assembly allows the formation of nanocrystalline films of controlled thickness on polar substrates. In general, mesoporous materials have the advantage of benefiting from a unique combination of structural, chemical and physical properties. This Perspective article addresses the structural characteristics and the electrical (charge-transport) properties of mesoporous metal oxides and how these affect their application in energy storage, catalysis and gas sensing.